Strategi Pengajaran Tuhan Yesus Berdasarkan Injil Matius Bagi Pola Pembentukkan Jemaat Rumah - Ledi, Roslina Soli; Sukarna, Timotius; Sihombing, Mangapul (Sekolah Tinggi Teologi Kadesi Bogor, 2025)
This article discusses the importance of Jesus' teaching strategy in the Gospel of Matthew for the formation of house congregations. Strategy comes from the Greek word stratogos, which means a method, procedure, or trick applied to achieve a goal and to shape the character of its mature members. In improving the quality of Jesus' teaching, Jesus used strategy and it became very effective in the Gospel of Matthew. The problem in this study is how Jesus' teaching strategy for house congregations based on the Gospel of Matthew actualizes their faith in the midst of the majority. Through a qualitative approach with theological analysis and biblical studies of chapters such as Matthew 4:19-20, Matthew 9:35, Matthew 5:2, Matthew 14:29, and Matthew 28:19-20. This article emphasizes that in Jesus' teaching, He prepared His disciples through a personal approach. The Lord Jesus not only chose disciples but also took responsibility for teaching them to prepare them to become teachers for others in spreading the Gospel. Jesus trained His disciples by involving them in real and active actions such as Jesus telling Peter to walk on water. The Lord Jesus performed signs and miracles before them with the sole purpose of training His disciples. The Lord Jesus also trained and taught them how to truly pray (Matthew 6:5-13). A house congregation is a group of people who gather and learn the truth of God's Word and participate in the proclamation of the Gospel. This means that the congregation is involved in spreading the good news about Jesus Christ, and the congregation perseveres in prayer and makes prayer a lifestyle. Therefore, Jesus' teaching in the Gospel of Matthew emphasizes the formation of a close community, experiential teaching, commissioning for ministry, and leading by example in daily life. Jesus not only taught in formal meetings but also built a close community with His disciples, who became models for the house congregation. Jesus chose, taught, trained, educated, and discipled His disciples by sending them out to serve directly. Jesus taught spiritual values through concrete actions, which confirms that the formation of a congregation is not only based on doctrine but also on living examples.